Fortification of blackcurrant juice with crowberry: Impact on polyphenol composition, urinary phenolic metabolites, and postprandial glycemic response in healthy subjects - Riitta Törrönen; Gordon J. McDougall; Gary Dobson; Derek Stewart; Jarkko Hellström; Pirjo Mattila; Juha-Matti Pihlava; Ali Koskela; Reijo Karjalainen (Journal of Functional Foods, 2012)
Functional drinks enhanced with putatively bioactive polyphenols are receiving extensive interest due to their potential health benefits. A randomized, controlled, double-blind cross-over study design was used to assess postprandial glycemic responses to a basic blackcurrant juice and a blackcurrant juice fortified with crowberry powder (respective polyphenol contents 159 and 293 mg/100 mL), both sweetened with sucrose. Concurrently, we studied the presence of polyphenol-derived metabolites in plasma and urine to confirm their bioavailability. Urinary metabolites characteristic of cyanidin anthocyanins (such as dihydroxybenzoic acid sulphate and dihydroxyphenylacetic acid sulphate) increased after intake and were present in higher levels after intake of the fortified juice. Compared to the basic juice, the fortified juice elicited slightly attenuated and sustained plasma glucose and insulin responses. In conclusion, fortification of blackcurrant juice with crowberry doubled the polyphenol content and improved postprandial glycemic control in healthy subjects. This gives encouragement for further functional food development.